Raven's Nest (48SU3871): A late prehistoric/Shoshone lithic tool and pottery-making site in Southwestern Wyoming. (2nd January 2017) - Hill, David V.; Wolfe, David
Abstract : Early Archaic to Historic occupations were unearthed during excavations at the Raven's Nest (48SU3871). Excavation of 135 1 × 1 m units in 15 discrete areas within Raven's Nest resulted in the recovery of over 21, 000 pieces of debitage, over 9000 faunal specimens, over 1100 prehistoric sherds and over 300 tools, including ca. 50 projectile points with the primary occupations occurring during the Late Prehistoric and Early Historic Periods. The Raven's Nest site likely functioned as a locality where stone tools and ceramics were produced by Numic-speaking peoples most likely the Shoshone. The predominance of three types of locally available tool stone in the lithic assemblage and their presence as raw material, flakes and finished tools indicates are indicative of stone tool production. On-site pottery-making activities at the Raven's Nest were identified by the large ceramic assemblage recovered from the site, the paste of the majority of the ceramics contain the same minerals that are present in the local clays and outcrops as determined through petrographic analysis, the presence of kiln wasters, and the recovery of a vessel form made using local clay that is not documented in ethnographies of the Shoshone.